2017
DOI: 10.5301/hipint.5000533
|View full text |Cite
|
Sign up to set email alerts
|

Improving registration accuracy during total hip arthroplasty: a cadaver study of a new, 3-D mini-optical navigation system

Abstract: This study demonstrates that the registration error associated with this new mini-navigation system compares favourably with the known registration error associated with traditional navigation systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 44 publications
2
10
0
Order By: Relevance
“…Furthermore, in the supine DAA group 1 cup had to be excluded from the final analysis, reducing the number of cups analyzed. Nonetheless, these numbers are comparable to previously published cadaveric studies [5,37]. Also, the TTM of patient registration is a novel method that may require a learning phase before a surgeon becomes proficient in the technique.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Furthermore, in the supine DAA group 1 cup had to be excluded from the final analysis, reducing the number of cups analyzed. Nonetheless, these numbers are comparable to previously published cadaveric studies [5,37]. Also, the TTM of patient registration is a novel method that may require a learning phase before a surgeon becomes proficient in the technique.…”
Section: Discussionsupporting
confidence: 87%
“…Sendtner et al [31] showed similar accuracy and precision in their study with a mean error of 0.37° (SD 3.26°) for inclination and −5.61° (SD 6.48°) for anteversion. In a cadaveric study using an accelerometer-based navigation system, Cross et al [5] compared navigation to CT imaging and found a mean absolute error of 4.2° and 4.0° for inclination and version, respectively. In our current study, the mean absolute error was 2.3° and 4.1° for inclination and version, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CT scans of six cadavers (one female, five male) used in previous THA studies [21][22][23] and 14 patients (nine female, five male) undergoing primary THA were obtained using a GE LightSpeed™ 16 imager (GE Healthcare, Chicago, Illinois; 140 kV, 600 mA at 0.8 sec revolution time and 0.625 mm slice thickness). Each CT scan was segmented using medical image computing software (3-D Slicer, version 4.6 [24]).…”
Section: Ct Scansmentioning
confidence: 99%
“…However, this observation corresponds with a report by Chechik et al [28] that indicates the direct anterior approach is less used in the United States, and the authors could not control for this retrospectively. Intraoperative device HCOR measurements are relative to the patient positioning captured at the time of registration; therefore, any deviations from the true patient position at registration may be reflected when capturing HCOR [29,30]. This is of particular importance with respect to the small yet significant difference in A-P HCOR displacement observed between anterior and lateral/posterior cases.…”
Section: Discussionmentioning
confidence: 99%